Investigating the adverse impacts of rural roads using a fuzzy multicriteria approach - Tirth, Vineet; Wagale, Makrand; Singh, Ajit Pratap; Sarkar, Ashoke Kumar; Singh, Ram Karan; Algahtani, Ali; Islam, Saiful (Journal of Civil Engineering and Management, 2021)
Rural roads contribute significantly to the living conditions of rural populations. However, they also lead to detrimental impacts on physical and social environments. In this context, the present study proposes a novel fuzzy multicriteria approach that amalgamates fuzzy TOPSIS and an improved fuzzy weighted average method to assess the negative impacts on physical and social environments, due to rural road construction. The approach offers a structured comprehension and incorporates detailed criteria that reflect the adverse effects. The attributes identified and assessed in this study are air quality, vegetation cover status, noise pollution, transmissible disease, habits/behaviour, safety and security, and road accidents. The approach includes both qualitative and quantitative data from focus group discussions. The results presented here are essential to identify corrective actions, promote effective distribution of funds, and facilitate effective decisionmaking for sustainable rural development.